2022
DOI: 10.1101/2022.06.20.22276205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohort Profile: Longitudinal population-based study of COVID-19 in UK adults (COVIDENCE UK)

Abstract: Background: Coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is estimated to have caused more than 18 million deaths worldwide as of end-May 2022. Methods: COVIDENCE UK is a longitudinal population-based study that investigates risk factors for, and impacts of, COVID-19 in UK residents aged ≥16 years. A unique feature is the capacity to support trial-within-cohort studies to evaluate interventions for prevention of COVID-19 and other acute … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The study was launched on 1 May 2020 and closed to recruitment on 6 October 2021; a total of 19 981 participants enrolled. 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was launched on 1 May 2020 and closed to recruitment on 6 October 2021; a total of 19 981 participants enrolled. 26 …”
Section: Methodsmentioning
confidence: 99%
“…COVIDENCE UK was established to determine risk factors for incident covid-19,1213 characterise the clinical course of the disease, evaluate impacts of covid-19 on physical and mental health and economic vulnerability,25 and provide a platform from which to conduct clinical trials of interventions to reduce the incidence and severity of acute respiratory tract infections. The study was launched on 1 May 2020 and closed to recruitment on 6 October 2021; a total of 19 981 participants enrolled 26…”
Section: Methodsmentioning
confidence: 99%
“…As many countries are facing ageing populations, longitudinal studies on the effects of ageing have been established to improve the health-care needs in older adults 14 and assess the effect of the COVID-19 pandemic. 4 , 15 , 16 However, few countries, if any, combine epidemiological data on comorbidities, frailty, function, and lifestyle factors with sequential in-depth immunological data to explore the effects of infection and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-study 1 (vaccine efficacy analysis) investigated the influence Full details relating to the design and conduct of the CORONAVIT trial and postvaccination serology studies have been reported elsewhere [17,21]. Briefly, 6200 UK residents aged 16 years or older and participating in the COVIDENCE UK study [23] were individually randomised to receive an offer of a postal vitamin D test, followed by higher-dose (3200 IU/day; n=1550) or lower-dose (800 IU/day; n=1550) vitamin D supplementation if their blood 25(OH)D concentration was found to be less than 75 nmol/L, or to receive no offer of vitamin D testing or supplementation (n=3100), with a 1:1:2 allocation ratio. Treatment allocation was not concealed, and randomisation was not stratified.…”
Section: Methodsmentioning
confidence: 99%